Feasibility of repetitive transcranial magnetic stimulation on non-motor symptoms of spinocerebellar ataxia type 3: a secondary analysis of a randomized clinical trial - Wu, Hua; Xu, Hao-Ling; Liu, Xia-Hua; Sikandar, Arif; Lin, Wei; Cui, Mao-Lin; Kang, Ming-Xia; Zheng, Yi-Ru; Gan, Shi-Rui; Qiu, Liang-Liang (Frontiers in Neurology, 2025)
IntroductionSpinocerebellar ataxia type 3 (SCA3) poses challenges for patients due to motor dysfunctions and non-motor symptoms (NMS), such as sleep disorders, cognitive deficits, and mood disturbances. These issues significantly impact the quality of life, with limited benefits from conventional pharmacotherapies. This study explores the potential of repetitive transcranial magnetic stimulation (rTMS) as a treatment for SCA3-related NMS.MethodsThis is a secondary analysis of a randomized, double-blind, sham-controlled trial (The Chinese Clinical Trial Registry identifier is ChiCTR1800020133). Thirty-seven SCA3 patients included underwent either real (n = 21) or sham (n = 16) rTMS over 15 days, targeting the cerebellum. Study outcomes included the Pittsburgh Sleep Quality Index (PSQI), Athens Insomnia Scale (AIS), Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Hamilton Anxiety Rating Scale (HARS), and Hamilton Depression Rating Scale (HDRS), assessed baseline and post-intervention.ResultsThe results disclosed significant time effects for all the outcomes with post hoc comparisons showing differences of baseline and post-treatment evaluation, with decreases for PSQI, AIS, HARS, and HDRS as well as increase for MMSE and MoCA. Correlation analyses revealed no significant predictors of rTMS response based on age at onset, disease duration, number of expanded CAG repeat lengths, or baseline motor symptom severity scores.ConclusionRepetitive transcranial magnetic stimulation is a feasible treatment of non-motor related symptoms in patients with SCA3, including sleep, cognition, and mood disorders. The treatment is well-tolerated, and its feasibility appears independent of demographic or disease severity indicators. These findings encourage further exploration of rTMS as a safe alternative for managing SCA3 NMS.